INFORMATION AND ATTITUDE SHIFTS: HOW COVID-19-INDUCED INEQUALITIES SHAPE PUBLIC SUPPORT FOR GOVERNMENT INTERVENTION - Nyhan, B.; Reifler, J (Journal of Current Research and Review (JCRR), 2022)
The increase in economic inequality since the 1970s has puzzled scholars of public opinion, as there is limited attitudinal evidence of concern or calls for income redistribution among the public despite growing support for government intervention. This phenomenon is often attributed to widespread misperception of economic disparities and the non-meritocratic nature of inequality. However, addressing these misperceptions through factual information is challenging due to ideological distrust, differential exposure to information, and partisan motivated reasoning. This paper investigates belief change during the COVID-19 crisis, specifically examining whether information on COVID-19-induced inequalities heightens the public’s concern about inequity and strengthens support for government intervention, and how partisanship shapes the uptake of information. The study employs a survey experiment methodology in the United States, known for its high levels of economic inequality, limited support for income redistribution, and deep political polarization. The results indicate that learning about COVID-19-induced inequalities increases acknowledgment of the pandemic’s impact on the most vulnerable, enhances concerns about economic inequality, and boosts support for income redistribution. Notably, the effects are more pronounced among moderate Republicans, reducing the partisan gap between moderate Democrats and Republicans while widening the gap between moderate and strong Republicans. These findings demonstrate that providing uniform crisis information can elevate concerns about inequality among significant segments of the population and bridge attitudinal gaps among moderate partisans in a highly polarized country. The study contributes to the literature on crises, political polarization, and informational interventions, and offers implications for other country contexts.